RHINOXENUS BULBOVAGINATUS (MONOGENEA, DACTYLOGYRIDAE) PARASITE OF THE NASAL CAVITIES OF SALMINUS HILARII (CHARACIFORMES, CHARACIDAE) IN A NEOTROPICAL RIVER, SP, BRAZIL - Bravin Narciso, Rodrigo (2013)
The aim of study is to report for the first time the occurrence of Rhinoxenus bulbovaginatus infesting the nasal cavity of Salminus hilarii from the Taquari River, São Paulo State, Brazil. Rhinoxenus bulbovaginatus was originally described parasitizing the nasal cavities of Salminus brasiliensis from the Paraná River. Rhinoxenus spp. are monogenean parasites from the nasal cavities of Characiformes fishes in the Neotropical region. To date, eight species of Rhinoxenus were described in seven different hosts. This study broadens the range of hosts parasitized with monogeneans of nasal cavities.